PENGARUH PRINSIP–PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA KEUANGAN LEMBAGA PERKREDITAN DESA DI KABUPATEN BADUNG - Bulandari, I Gusti Agung Wita; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi; Vol 8 No 3 (2014), 2015)
Lembaga Perkreditan Desa (LPD) in Bali intermediation function through the acceptance of savings and lending. LPD to be something important because LPD is a community liaison and administration. LPD therefore must be declared fit to be protective of the public in general. LPD must maintain the existence and declared himself healthy by using the application of the concept of good corporate governance. This research was conducted in Badung Regency Village Credit Institutions. The number of samples taken by 107 healthy LPD using non-probability sampling technique purposive sampling method. Using the tools of SPSS 17 for windows. The results of this study are positively openness, accountability, responsibility, independence and fairness affect the financial performance of Badung Regency Lembaga Perkreditan Desa (LPD).
Keywords: transparency, accountability, responsibility, independence, kewajaraan, financial performance